Imperial statues and subaltern groups: destruction, ridicule and criticism as subversion of power relations in Late Antiquity - Ocón, Jorge Elices; Silva, Glaydson José da (Romanitas - Revista de Estudos Grecolatinos, 2022)
In this article we propose to analyze the relationship of the subaltern groups with imperial statues during the last centuries of the Ancient World (IV-VIII), pointing to examples of subversive and critical readings of imperial power documented in the sources, which point out that the subaltern groups developed new ways of redefining traditional power relations from the way they interacted with imperial statues.
Keywords: Iconoclasm; Mutilation; Urban riots; Damnatio memoriae; Parastaseis